2022
DOI: 10.3390/cells11091569
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea as a Risk Factor for COVID-19 Severity—The Gut Microbiome as a Common Player Mediating Systemic Inflammation via Gut Barrier Dysfunction

Abstract: The novel corona virus that is now known as (SARS-CoV-2) has killed more than six million people worldwide. The disease presentation varies from mild respiratory symptoms to acute respiratory distress syndrome and ultimately death. Several risk factors have been shown to worsen the severity of COVID-19 outcomes (such as age, hypertension, diabetes mellitus, and obesity). Since many of these risk factors are known to be influenced by obstructive sleep apnea, this raises the possibility that OSA might be an inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 110 publications
0
10
0
3
Order By: Relevance
“…Previous studies ( Yonker et al, 2021 ; Giron et al., 2021 ; Oliva et al., 2021 ) have linked higher intestinal translocation with severe cases of COVID-19, describing a higher abundance of bacterial components in the bloodstream compared to milder cases. It has been suggested that microbial translocation, intestinal dysbiosis and underlying inflammatory processes might have a synergistic effect on systemic inflammation and high cytokine levels described in severe COVID-19 infections ( Cardinale et al., 2020 ; Vignesh et al., 2020 ; Uzzan et al., 2020 ; Mashaqi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies ( Yonker et al, 2021 ; Giron et al., 2021 ; Oliva et al., 2021 ) have linked higher intestinal translocation with severe cases of COVID-19, describing a higher abundance of bacterial components in the bloodstream compared to milder cases. It has been suggested that microbial translocation, intestinal dysbiosis and underlying inflammatory processes might have a synergistic effect on systemic inflammation and high cytokine levels described in severe COVID-19 infections ( Cardinale et al., 2020 ; Vignesh et al., 2020 ; Uzzan et al., 2020 ; Mashaqi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of subjects genetically predisposed to autoimmune diseases, changes in the structure and function of their intestinal microbiota caused by environmental factors will disrupt the function of the zonulin-dependent intestinal barrier (inadequate control of antigen flows), i.e., zonulin-dependent loss of the intestinal mucosal barrier, leading to “leaky gut” or the “permeable intestine” and a dysfunctional immune response of the mucosa, with implications for autoimmunity and chronic inflammatory diseases [ 134 , 139 , 142 , 143 , 144 ].…”
Section: Molecular Mechanisms Of Sars-cov-2 Infection and How CD Led ...mentioning
confidence: 99%
“…9 Since then, several studies have reported the strong association between respiratory viruses such as adenoviruses, SARS-CoV-2 and other coronaviruses, and other ubiquitous viral pathogens and the prevalence of OSA in children. [10][11][12][13][14][15][16] The reverse relationship between viral infections and OSA that addresses the question of whether the presence of OSA adversely affects the clinical course and outcomes of a viral disease has also elicited substantial interest in recent years, particularly following the advent of the COVID-19 pandemic. 11,14,[16][17][18][19][20] Such intriguing supposition has been fostered by the realization that altered sleep patterns, such as those occurring in the context the sleep fragmentation induced by the presence of OSA and other sleep disorders, modify the immune response and may lead to an enhanced systemic and organ-specific inflammatory response to viral antigens along with reduced adaptive responses to vaccines.…”
Section: Obstructive Sleep Apnea and Respiratory Viruses In Children:...mentioning
confidence: 99%
“…[10][11][12][13][14][15][16] The reverse relationship between viral infections and OSA that addresses the question of whether the presence of OSA adversely affects the clinical course and outcomes of a viral disease has also elicited substantial interest in recent years, particularly following the advent of the COVID-19 pandemic. 11,14,[16][17][18][19][20] Such intriguing supposition has been fostered by the realization that altered sleep patterns, such as those occurring in the context the sleep fragmentation induced by the presence of OSA and other sleep disorders, modify the immune response and may lead to an enhanced systemic and organ-specific inflammatory response to viral antigens along with reduced adaptive responses to vaccines. [21][22][23] In a large number of studies focused on this particular question, the underling presence of OSA and its magnitude seem to mediate the risk of hospital admission, overall severity of clinical manifestations, and also adversely affect both short-term and long-term complications.…”
Section: Obstructive Sleep Apnea and Respiratory Viruses In Children:...mentioning
confidence: 99%